FENOMENA TA’ARUF ONLINE PERSPEKTIF HUKUM ISLAM SERTA DAMPAK POSITIF DAN NEGATIF BAGI PENGGUNA APLIKASI KENCAN - Muhammad Syafi'i Najmi; Lisa Herlina; Fitriani Ullul Azmi (MAQASHIDUNA: Jurnal Hukum Keluarga Islam, 2026)
The purpose of this research is to analyze the pros and cons of online ta'aruf from an Islamic legal standpoint, and to draw conclusions about its effect on marriage.  This study employs a qualitative methodology by analyzing the ta'aruf process through the lens of four madhhabs' perspectives on marriage and fraud as well as Qur'anic verses and fiqh regulations.  According to the findings, Islamic law permits online ta'aruf as long as it follows sharia adab, which includes not being alone without a mahram, keeping one's intentions, and having a marriage as the goal. The benefits include making it easier to locate a mate, growing one's social circle, and screening out those who don't share one's worldview. Negative effects include over-reliance on technology, the possibility of identity theft involving personal information (such as name, employment, religion, marital status, and health), and transgressions in social norms about interactions between the sexes.  Based on the nature and degree of the deceit, divorce (fasakh) or consequences for the marital contract's legality may result from such dishonesty in fiqh.  Therefore, in order to adhere to the norms of Islamic law, the use of online ta'aruf programs necessitates supervision, good intentions, and prudence.